Hyperbaric oxygenation and glucose/amino acids substitution in human severe placental insufficiency - Tchirikov, Michael; Saling, Erich; Bapayeva, Gauri; Bucher, Michael; Thews, Oliver; Seliger, Gregor (Wiley Open Access, 2018)
In the first case, the AA and glucose were infused through a perinatal port system into the umbilical vein at 30 weeks' gestation due to severe IUGR. The patient received daily hyperbaric oxygenation (HBO, 100% O2) with 1.4 atmospheres absolute for 50 min for 7 days. At 31+4 weeks' gestation, the patient gave birth spontaneously to a newborn weighing 1378 g, pH 7.33, APGAR score 4/6/intubation. In follow‐up examinations at 5 years of age, the boy was doing well without any neurological disturbance or developmental delay. In the second case, the patient presented at 25/5 weeks' gestation suffering from severe IUGR received HBO and maternal AA infusions. The cardiotocography was monitored continuously during HBO treatment. The short‐time variations improved during HBO from 2.9 to 9 msec. The patient developed pathologic CTG and uterine contractions 1 day later and gave birth to a hypotrophic newborn weighing 420 g. After initial adequate stabilization, the extremely preterm newborn unfortunately died 6 days later. Fetal nutrition combined with HBO is technically possible and may allow the prolongation of the pregnancy. Fetal‐specific amino‐acid composition would facilitate the treatment options of IUGR fetuses and extremely preterm newborn.
Keywords: Amino acids; cordocentesis; fetal growthrestriction; HBO; hyperbaric oxygenation; intrauterine treatment; intravenous infusion; IUGR; placental insufﬁciency; portimplantation